Rio Sibimbe como recurso natural y su incidencia en la promoción turística de la parroquia Los Ángeles del cantón Ventanas provincia de los Ríos - Vega Rodríguez, Solange Jimena (2018)
Natural resources play an important role in tourism projects worldwide and as a reservoir of flora and fauna life, in Ecuador this sector has been exploited very little in tourism, rural sectors that have such attractiveness have lacked support and its development has been slow according to the effort and work of its inhabitants. In the present research work is intended to analyze the situation of the Sibimbe River as a natural resource for tourism development of the Los Angeles parish of the Ventanas canton, for which documentation concerning the work developed by the municipal GAD for the benefit of rural tourism was reviewed. surveys and interviews were applied to the inhabitants of the sector, to tourists and to the employees and owners of the tourist places, which evidenced the deficient state work and the scarce or null investment both public and private in this sector. After analyzing the results, the implementation of the alternative proposal for the tourism promotion plan for the Sibimbe River was highlighted through different techniques integrated with the technology and insertion of practice of recreational activities for tourists.